PERBANDINGAN METODE DEDISCERTA DENGAN METODE SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) DALAM KEMAMPUAN MEMBACA PEMAHAMAN TEKS CERITA RAKYAT DAN HASIL BELAJAR SISWA KELAS V GUGUS 3 KECAMATAN BONTONOMPO KABUPATEN GOWA - Alam, Nur; Azis, Sitti Aida; Bahri, Aliem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the comparison of the Dediscerta Learning Method with the Survey, Question, Read, Recite, Review (SQ3R) Learning Method in Reading Ability, Comprehension of Folklore Texts and Learning Outcomes of Class V Cluster 3 Students, Bontonompo District, Gowa Regency. This research aims to determine whether there are differences in students' reading comprehension abilities of folklore texts using the Dediscerta learning method and the SQ3R learning method. The type of research used is quasi experimental design type nonequivalent control group design. The research population was all students of class V, Cluster 3, Bontonompo District, Gowa Regency, which consists of seven schools with a total number of students of 285. The research sample chosen was class V students of SDI Ta'buakkang, totaling 44 people. There are 42 class V students at SDI Bilonga. There were 45 class V students at SDN Bategulung using cluster random sampling techniques. The data collection technique in the research was carried out through a test technique to determine students' ability to read and understand folklore texts in the form of multiple choice questions totaling 10 questions.The results of research based on descriptive analysis showed that the average value of the Dediscerta learning method at SDI Ta'buakkang was 85.23, at SDI Bilonga 81.75 at SDN Bategulung, 81.59, while for the application of the SQ3R learning method at SDI Ta'buakkang, the average value was 83. .57 at SDI Bilonga 81.75 at SDN Bategulung 81.42. This means that the Dediscerta learning method is more improved than the SQ3R learning method. Meanwhile, the results of the inferential analysis show that the Dediscerta learning method has a more significant effect compared to the SQ3R learning method on the ability to read and understand folklore texts for class V group 3 students in Bontonompo District, Gowa Regency. This is based on the results of the independent sample t test obtained, namely the sig value. 0.001 < 0.005.   Keywords: dediscerta learning method, SQ3R, reading comprehension ability, learning outcomes